"The Cloven Hoof under the Cassock": Sacrifice Hidden in the Hebrew Bible and Roger Scruton. (3rd April 2023) - Morrissey, Christopher S.
Abstract: A typology of sacrifice is applied to the study of Roger Scruton's religious philosophy, in order to contemplate the ways in which dissidence against totalitarianism can become a positive form of self-giving. The mimetic theory of René Girard can help us to see how totalitarianism creates a sacrificial crisis by demanding, on the one hand, that individuals sacrifice themselves for the regime, and yet, on the other hand, empties such sacrifices of the type of self-giving that makes a sacrifice not just efficacious but also nonviolent. The deprivations that a regime inflicts on its subjects, for example with respect to education and careers, are enforced forms of sacrifice. With respect to the self-giving enacted in visible dissidence, there is a performative dimension to such self-giving that brings both sacrifices and rewards of a public nature. In his novel, Notes from Underground, Scruton explores the private, underground world of people who are excluded even from such careers of public dissidence. The difficult question Scruton confronts is how any regenerative self-giving is possible among people who in their isolation and powerlessness have nothing to give. While Girard's mimetic theory helps account for the systematic desecration at work in totalitarian cultures, the biblical typology of sacrifice offered by Moshe Halbertal in his disagreement with Girard offers improvements to such a theoretical framework. Halbertal's typology of sacrifice better accounts for the instances of spiritual transcendence considered by Scruton in his novel, and also in Scruton's posthumous final work, Wagner's Parsifal: The Music of Redemption .